TUC mobile canteen, 1940 (1940)
1940 1939-1945 "TUC mobile canteen, 1940" [HFR0026], 1940 During the war, the TUC and individual unions funded a fleet of more than 50 mobile canteens and cinema vans to provide a service for H.M. Forces, overseas or based in isolated anti-aircraft units or searchlight stations. The canteens, organised by the Y.M.C.A., also operated in blitzed areas. The scheme was launched at Buckingham Palace on 26 November, 1940 when King George VI inspected the canteens and was presented with the Gold Badge of Congress. This vehicle was presented to the TUC scheme by the Amalgamated Engineering Union.